Management of marine tourism park based on Community Based Management (CBM) - Putriani, Rizha Bery; Hasani, Qadar; Yudha, Indra Gumay; Diantari, Rara; Yuliana, Darma; Caesario, Rachmad; Reza, Muhammad; Julian, David (JURNAL MINA SAINS, 2024)
This research was conducted in Kiluan Village, Kelumbayan District, Tanggamus Regency. This study examines the essence of managing marine park tourism by focusing on the surrounding environment (Community-based Management) in Kiluan Negeri, Tanggamus Regency. The research was conducted by descriptive analysis of qualitative approaches through direct studies (primary data) and existing data (secondary data). Kilian Negeri has beautiful and unique marine resources. Problems in Kiluan Bay are related to economic inequality, limited resources, environmental damage due to garbage, and the threat of natural disasters. The general public still needs to learn how involved they are in managing marine park tourism appropriately and sustainably. The active participation of NGOs, namely the NGO Cikal, plays an important role in managing the Kiluan Bay conservation area. Some Community-Based Management (CBM) strategies that can be done are preparing tourism development plans, developing infrastructure, managing tourist destinations, holding promotions and marketing, developing tourism products, conducting HR training, collaborating with the private sector, and developing integrated tourist areas. Community-based management (CBM) of marine park tourism is based on recognizing the importance of local communities in maintaining the sustainability of the marine environment and obtaining economic and social benefits from the tourism sector.